Patient empowerment, eating behaviours and illness control: pre-post outcomes from DWELL delivery in UK and France. (30th September 2020) - Morris, R; Hatzidimitriadou, E; Manship, S; Hulbert, S; Webster, J; Teke, J; Belmas, N; Best, A; Averous, V; Cazier, J
Abstract: Diabetes self-management programmes can improve clinical and healthy lifestyle outcomes. Research has demonstrated that improved engagement with type 2 diabetes (T2D) care is associated with greater empowerment beliefs and a perceived internal control over their illness. As part of the DWELL evaluation study, an interim subset of 139 participants in the UK and 53 participants in France were assessed pre- and post-intervention on measures of weight, BMI, waist circumference and glycated haemoglobin (HbA1c), as well as self-efficacy beliefs (DES-SF), healthy eating behaviours (DEBQ) and perceptions of illness (IPQ-R). Pre-post comparisons in both countries demonstrated statistically significant decreases in weight (UK: Z = 6.71, p<.001, FR: Z = 3.33, p<.05), BMI (UK: Z = 6.70, p<.001, FR: Z = 3.21, p<.05), waist circumference (UK: Z = 6.71, p<.001, FR: Z = 3.24, p<.05), and HbA1c (UK: Z = 6.29, p<.001, FR: Z = 4.18, p <.001). Importantly, participation in the DWELL programme was associated with increased self-efficacy beliefs (UK: Z = 5.63, p<.001, FR: Z = 5.54, p<.001), greater perceived personal control over their diabetes (UK: Z = 3.17, p<.05, FR: Z = 2.20, p<.05), reduced negative feelings about their illness (UK: Z = 3.01, p <.05, FR: Z = 2.19, p<.05) and decreased eating in response to external food cues (UK: Z = 3.79, p<.001, FR: Z = 2.34, p<.05). In the UK, participants also reported an increased optimism for treatment control of their diabetes (Z = 3.06, p <.05) and for their long-term prognosis (Z = 1.99, p<.05).These preliminary findings support the efficacy of the DWELL programme in improving diabetes-related biomedical outcomes, as well as improvements in patient empowerment, healthy eating habits and increased perceived illness control. Further analysis, available at a later date, will include a larger sample of participants, including longitudinal data with follow-ups six- and 12- months post participation in the DWELL programme.